Asymmetries of the balanced SSFP profile. Part I: theory and observation. - Miller, K (2010)
The signal in balanced steady-state free precession has a strong sensitivity to off-resonance, which is typically described in terms of a signal "profile" over a range of frequencies. This profile has a well-known form for homogeneous media with a single T(1), T(2), and resonance frequency, which is symmetric about the on-resonance frequency. However, a straightforward extension to this established signal model predicts that the profile may become asymmetric in the presence of inhomogeneous frequency content, as would be expected to happen in tissue due to microstructural boundaries, compartments, and chemical shift. The presence of asymmetries in the balanced steady-state free precession profile may therefore provide a marker of tissue integrity. This manuscript describes the theory behind balanced steady-state free precession asymmetries, a method for detecting these effects, and the first measurements of balanced steady-state free precession asymmetries in tissue. Asymmetries are found in gray matter, white matter, and muscle, with excellent reproducibility. A companion paper considers the large white matter asymmetries in more detail.